Konversi CO2 Menjadi Metana Menggunakan Katalis Ni-Zn/Al2O3 Ditinjau dari Kemampuan Katalis dan Waktu Operasi - Wijaya, Satria Agung; Junaidi, Robert; Hasan, Abu (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Carbon dioxide (CO2) gas is a gas that can be a threat to the environment because its emissions continue to increase from year to year. Therefore, this research aims to utilize CO2 gas and convert it to methane gas (CH4) using a fixed bed reactor type reactor containing a catalyst. In this study, the CO2 methanation process was carried out with the help of Ni/Al2O3 catalyst supported with Zn metal in situ. This study varies the catalyst treatment denoted by Ni_R0 - Ni_R4, with the amount of catalyst as much as 50 grams and variations in the operating time of the CO2 methanation process for 70 minutes and 80 minutes. The highest methane gas yield of 50.11% was obtained in sample 10 with the Ni_R4 catalyst treatment variation (Ni_R0 - Ni_R4 variation) for 80 minutes (70 minutes and 80 minutes variation). The longer the methanation process, the longer the contact process between CO2 gas and NaOH solution.